1995
DOI: 10.1093/hmg/4.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of germline mutations in the RB1 gene: a study of 232 patients with hereditary and non hereditary retinoblastoma

Abstract: Germline mutations in the RB1 gene confer hereditary predisposition to retinoblastoma. We have performed a mutation survey of the RB1 gene in 232 patients with hereditary or non hereditary retinoblastoma. We systematically explored all 27 exons and flanking sequences as well as the promotor. All types of point mutations are represented and are found unequally distributed along the RB1 gene sequence. In the population we studied, exons 3, 8, 18 and 19 are preferentially altered. The range of frequency of detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 0 publications
9
78
0
2
Order By: Relevance
“…Conversion of codon 817 or codon 835 into a premature stop (Liu et al, 1995;Lohmann et al, 1996) and the insertion of two nucleotides resulting in a stop codon following amino acid 825 have been described (Blanquet et al, 1995). The recurrent identification of mutations leading to the loss of C-terminal pRB sequence in retinoblastoma patients, along with the demonstration of loss of functioning in pRB-DELTA exons 24-25, displaying partial loss of C-terminal sequence, provides a strong argument for a disease causing effect of such mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of codon 817 or codon 835 into a premature stop (Liu et al, 1995;Lohmann et al, 1996) and the insertion of two nucleotides resulting in a stop codon following amino acid 825 have been described (Blanquet et al, 1995). The recurrent identification of mutations leading to the loss of C-terminal pRB sequence in retinoblastoma patients, along with the demonstration of loss of functioning in pRB-DELTA exons 24-25, displaying partial loss of C-terminal sequence, provides a strong argument for a disease causing effect of such mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings infer a role for pRB in controlling cell homing and invasion, the paracrine management of tissue morphogenesis and the promotion of lineage specific differentiation. Recent work has emphasized the importance of pRBmediated gene activation and gene repression in the prevention of tumor formation, suggesting that these activities may cooperate towards achieving effective tumor suppression (Sellers et al, 1998).The common type of RB1 alteration in patients with retinoblastoma are nonsense mutations predicted to result in the generation of severely truncated pRB forms with complete loss of all functional domains Gallie, 1994;Blanquet et al, 1995;Cowell and Cragg, 1996;Lohmann et al, 1996;Yilmaz et al, 1998;Lohmann, 1999;Alonso et al, 2001;Najera et al, 2001;Houdayer et al, 2004). However, in some instance the alterations have more subtle consequences, including the change, deletion or insertion of single amino acids or the alteration of intronic sequences, which perturbs or prevents correct splicing of the transcript.…”
mentioning
confidence: 99%
“…They have been reported to vary from 10-20% in some reports 6 to around 89% in others, 7 using experimental procedures and selection criteria biased toward the inclusion of a large excess of bilateral cases. 7,8 Globally, RB1 gene mutations can be found in no more than 50% (low sensitivity) of all cases, according to some of the most recent reports 9 ; 2. they are commonly found in a great number of non retinoblastoma cancers 9,10 such as osteosarcoma, breast, bladder, lung, head and neck cancer, acute leukaemia, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: retinoblastoma; missense mutation; incomplete penetrance; SSCP Mutational analysis of the RB1 gene has shown that patients with the hereditary form of retinoblastoma (Rb) carry germline mutations within the gene Onadim et al, 1993;Blanquet et al, 1993Blanquet et al, , 1995Lohmann et al, 1994Lohmann et al, , 1996Shimizu et al, 1994). Hereditary cases are de®ned as individuals who have a family history of tumors or individuals without a family history but who have bilateral and/or multifocal tumors usually with an early age of onset.…”
mentioning
confidence: 99%
“…It has now become clear that the majority of mutations identi®ed in individuals with the severe phenotype usually generate premature stop codons (Blanquet et al, 1995;Liu et al, 1995;Cowell et al, 1994;Lohman et al, 1996), either as a result of single base pair mutations or following frame-shifts induced by insertions and deletions. Mutations a ecting splice sites have also been reported in about 30% of cases Liu et al, 1995;Lohmann et al, 1994) which are presumed to result in a non-functional protein.…”
mentioning
confidence: 99%